Development and validation of an analytical method for determination of pharmaceuticals in fish muscle based on QuEChERS extraction and SWATH acquisition using LC-QTOF-MS/MS system - Peña-Herrera, Juan Manuel; Montemurro, Nicola; Barceló, Damià; Pérez Solsona, Sandra (Talanta, 2019)
This study aimed at developing an analytical method for the extraction and quantification of 21 pharmaceutical actives compounds (PhACs) present in fish muscle. Using Norwegian Atlantic salmon as matrix, two extraction methods for PhACs were tested: ultrasound extraction (USE) using methanol (MeOH), acetonitrile (MeCN) or a mixture of MeCN:MeOH (1:1, v/v) as extracting solvents, and QuEChERS method using three different extraction salts. After selecting QuEChERS Original as extracting method of the analytes, three different clean-up methods were evaluated with respect to their efficiency to remove coextracted fat and lipids such as Enhanced Matrix Removal (EMR) and HLB prime. The dispersive-SPE EMR yielded the best recoveries for 21 of 27 analytes. PhACs were quantified by UPLC-MS/MS using SWATH acquisition mode. The method was validated in terms of recoveries, accuracy, linearity, precision, matrix effects at three levels of concentration: 25, 200 and 500 ng g−1 dw of fish muscle. For the majority of the analytes the recoveries were over 70%. Finally, the validated method was applied to natural riverine fish from the Evrotas river (Greece) and the Adige river (Italy) with positive findings for acetaminophen, propranolol, and venlafaxine reaching concentrations as high as 80 ng g−1 of muscle. © 2019 Elsevier B.V. This work was financially supported by European Communities 7th Framework Program funding under agreement No. 603629-ENV-2013-6.2.1 Globaqua. J.M. Peña-Herrera gratefully acknowledges Colciencias for his loan-scholarship financial support provided through Doctorate Scholarship Program (PDBC) “Doctorado Exterior–568”. We acknowledge SCIEX for providing the loan instrument LC/HRMS QTOF X500R and Bekolut GmbH & Co. KG is acknowledged for the contribution with QuEChERS kits extraction. The authors acknowledge Dr. Peter Eichhorn for his advices and support including language correction in the final manuscript. Peer reviewed